Congenital anomalies in Santa Catarina: case distribution and trends in 2010-2018 - Bruna Muraro Vanassi; Gabriel Cremona Parma; Vivyane Santiago Magalhaes; Augusto César Cardoso dos Santos; Betine Pinto Moehlecke Iser (Sociedade de Pediatria de São Paulo, 2021)
Abstract Objective: To evaluate the distribution of cases of congenital anomalies in the state of Santa Catarina by health macro-region, to determine the frequency according to maternal and neonatal variables, to estimate the related mortality, and the trends in the period 2010-2018. Methods: An ecological time-series study with secondary data on congenital anomalies and the sociodemographic and health variables of mothers and newborns living in Santa Catarina, from 2010 to 2018. For temporal trend analysis, generalized linear regression was performed using the Prais-Winsten method with robust variance. Results: The average prevalence of congenital anomalies in the period was 8.9 cases per 1,000 live births, being 9.4 cases by 1,000 live births in 2010 and, in 2018, 8.2/1,000. The trend remained stable in the analyzed period. The major malformations were musculoskeletal, hip, and foot malformations, with a proportion ≥30%. There was a higher prevalence of congenital anomalies in low birthweight, preterm, male livebirths with Apgar≤7, born by cesarean section, mothers of older age (≥40 years), and less educated (less than eight years of study). Infant mortality due to congenital malformations was 2.6 deaths/1,000 live births, representing about 25.8% of the total infant deaths in the period. Conclusions: The frequency of congenital anomalies and the mortality with anomalies was stable in the studied period in Santa Catarina. The presence of anomalies was associated with low birth weight, prematurity, and low Apgar score. The highest proportion of congenital anomalies was in the musculoskeletal system.